Educação a distância: o papel do professor nos cursos ministrados a distância - Laszkiewicz, Chafiha Maria Suiti (2012)
Distance education is very prominent in our society nowadays, not just because of the advance of communication and information on technology, but also by the increasing need of knowledge and training, upgrading and retraining to the professional area. This research assumes that only the available technologies in distance learning courses are not sufficiente to allow student´s success in the teaching-learning process. In this sense, our attention is all about the teacher, who works in virtual enviroments with the intent to promote meaningful learning throug mediation, dialogue and interaction that motivate satudentes to carry out the proposed activities, which further search and discussion, in orther to achieve not only the learning of some contents, but the development as a complete human being, cultural, historical, social and political aspects. Considering the importance of teacher s work this context, the aim of this study is to identify the necessary characteristics for such action. For this purpose, a survey was conducted with teachers and studentes who work in distant graduated courses at Universities to see and understand some peculiar chacteristics of this kind of work, as well to know the teacher´s profile who leads students to achieve the desired knowledge and training.